POTENCIALIDADES DIDÁTICAS DO MAPEAMENTO COLABORATIVO PARA A MOBILIZAÇÃO DE CONHECIMENTO GEOGRÁFICO PODEROSO NA ESCOLA - GANZ, TAYLENE MARCELE (2022)
This research is a case study, based on a participant observation with a qualitative approach. The study was conducted at Colégio Estadual Santo Antonio, located in Imbituva/PR and counted with the participation of 225 high school students. Through didactic sequences designed to be carried out with the use of the collaborative mapping platform Google My Maps, we sought to analyze what are the didactic potentialities presented by collaborative mapping for the mobilization of powerful geographic knowledge in school. As specific objectives we sought to identify potentialities and weaknesses found in the use of web mapping platforms as didactic tools in Geography teaching; to investigate whether collaborative mapping can sharpen students' geographic reasoning in relation to geographic situations related to them; analyze whether didactic practices with collaborative digital maps encourage in students more critical and reflective attitudes in relation to their reality and the production of their own knowledge; verify whether didactic sequences with collaborative maps lead students to the construction of powerful geographic knowledge and, finally, analyze whether the didactic use of collaborative maps can improve students' geographic thinking. The process of analyzing the data collected by the research was carried out through a qualitative-interpretative process in which we identified the existing patterns among the facts, extracted their meanings, and made the inferences and generalizations based on the categorical reference of Maude's (2016) Typology of Powerful Geographic Knowledge. Through this research, we verified that didactic processes developed with collaborative maps enhance students' geographic thinking, opportunizing the construction of powerful knowledge in school. From this perspective, collaborative digital maps become knowledge instruments capable of preparing students for life and encouraging more enlightened attitudes towards geographic situations, stimulating conscious decisions in relation to their own reality and strengthening the critical argumentation of the subjects.